MISWAK (SALVADORA PERSICA L) AS ORAL CARE ON VENTILATED PATIENTS IN ICU: A SYSTEMATIC REVIEW AND META ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - Muslim, Fariz Jauhar (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Ventilator-Associated Pneumonia (VAP) is a serious complication in patients receiving mechanical ventilation, as it increases mortality rates and prolongs length of stay in the ICU. Miswak (Salvadora persica L.), known for its antibacterial properties, has been considered as an alternative for oral care. This meta-analysis evaluated the effectiveness of miswak in preventing VAP through three randomized clinical trials that met the inclusion criteria. The findings showed that miswak demonstrated a VAP risk ratio approaching zero compared to chlorhexidine, with fewer adverse effects and better tolerability. The consistency of results across studies indicates potential clinical benefits. The most common regimen was twice daily use during the first three to five days of intubation, which was effective in preventing early bacterial colonization. These findings support miswak as a safe and economical oral care agent, and suggest it as a feasible alternative or adjunct to chemical antiseptics for VAP prevention in the ICU. However, further large-scale, multicenter studies are still needed to strengthen the scientific evidence and support the integration of miswak into evidence-based clinical practice guidelines.